(untitled) (Palíndromo, 2019)
The following research aims to clarify the meaning of contemporary cinematographic photography, locating it in social space-time, based on the texts of authors as Charlotte Cotton and Vilém Flusser, among others from several areas of knowledge such as communication, literature and anthropology, however, concerned with dealing with fictional narrative and symbolic interpretation. The fallowing ideas are holded mainly on the tripod: fiction, narrative and interpretation, emphasizing the construction of identity, the participation of the model and the public in the interpretation of a work and other features characteristic of the visual narrative that can be used by the author as a way of approaching the receiver. Throughout the text, some works were choosen to make considerations about its narrative and creation process, in order to exemplify the concepts discussed. As a result of the research, we have inserted some works of authorship, developed under the mantle of the concepts discussed.